Species richness and composition of macroalgal assemblages of a disturbed coral reef in the Gulf of California, Mexico - Piñon-Gimate, Alejandra; Chávez-Sánchez, Tonatiuh; Mazariegos Villarreal, Alejandra; Balart, Eduardo F.; Serviere-Zaragoza, Elisa (Instituto de Ecología, A.C., 2020)
Background and Aims: In September 2001, the coral reef of the San Lorenzo Channel, La Paz Bay, Gulf of California, Mexico, was affected by the stranding of the oil tank vessel “Lázaro Cárdenas II”. Soon afterwards, hurricane “Juliette” hit the area with strong winds and water movement, disturbing the reef again. After that, three zones could be observed in the reef: one directly impacted by the shipwreck, one indirectly impacted by the hurricane, which moved and accumulated the coral debris left by the shipwreck, and the third one, which was not impacted. Later, a monitoring program was established to determine the degree of recovery of macroalgal assemblages in both impacted zones compared with the non-impacted one. Methods: From February 2005 to December 2007, macroalgae were collected seasonally by scuba divers in the three zones. In each zone, three to five thalli of all conspicuous algae, five rocks and five fragments of dead coral covered with macroalgal turfs were collected. Species number and composition of macroalgae assemblages were compared between zones and between years. Key results: A total of 117 species were found, 70 belonged to the phylum Rhodophyta, 25 to Ochrophyta-Phaeophyceae, and 22 to Chlorophyta. Macroalgal species richness and composition of the impacted zones were not different from the control zone, even between years. Conclusions: Macroalgal assemblages in the San Lorenzo Channel coral reef were able to recover, regardless of the modification of the substrate caused by the stranding and the hurricane “Juliette” in 2001. Therefore, it is important to implement monitoring efforts in case of anthropogenic or natural disturbance to document the extension of damage, recovery of the communities, and propose mitigation strategies if necessary.